EMPLOYEE PERCEPTION IN THE REINVENTION OFORGANIZATIONAL BEHAVIOR MANAGEMENT AT THE HIGHER EDUCATION SERVICE INSTITUTE (LLDIKTI) REGION XVI - Irwan Halid; Asna Aneta, Eduart Wolok, Zuchri Abdussamad (Adisam Publisher, 2025)
This study aims to analyze employee perceptions regarding the approach of Reinventing Organizational Behavior Management at the Higher Education Service Institution (LLDIKTI), specifically in Region XVI. The research data was collected through interviews and observations and analyzed using an interactive model. The findings indicate that employee participation in the decision-making process within the LLDIKTI Region XVI work environment remains uneven. The study found that leadership figures, such as the Head of LLDIKTI Region XVI and Team Leaders, primarily control the decision-making process within LLDIKTI Region XVI. This results in lower-level staff merely accepting decisions that have already been made. While this approach may be more efficient in terms of time, it could significantly impact employees' perceptions of their roles if it continues over an extended period. Employees may develop sentiments of being undervalued or excluded from the formulation of policies, potentially leading to a decline in their motivation to contribute to the organization's goals. This, in turn, may result in apathy among employees, consequently hindering the organization's performance and preventing it from achieving its intended objectives. Increasing employee participation in decision-making would provide various stakeholders opportunities to contribute and assume responsibility for achieving organizational goals, thereby fostering a more engaged and accountable workforce.